Osteosarcopenia: epidemiology, molecular mechanisms, and management - Yi, Yong-Tao; Zhao, Hao-Fan; Wang, Wei-Zhou; Li, Xi (Frontiers in Endocrinology, 2025)
Osteosarcopenia (OS), a recently recognized syndrome characterized by the simultaneous occurrence of osteopenia/osteoporosis and sarcopenia, has emerged as an important concept in clinical practice. This integrated framework provides a comprehensive view of the musculoskeletal system, addressing a previously underappreciated aspect of muscle health. OS notably increases the risk of falls, fractures, hospitalization, and mortality in elderly patients with chronic diseases. Despite its growing clinical relevance, OS remains underdiagnosed, and its classification as a distinct syndrome is not universally accepted. The persistently high global prevalence of chronic diseases, along with their substantial medical, economic, and social burdens, underscores the urgent need for updated prevention and management strategies. This review advocates for greater awareness and improved management of OS in patients with chronic diseases. It examines the relationship between OS and chronic conditions, emphasizing its epidemiology, adverse outcomes, diagnostic approaches, pathophysiology, and potential management strategies.